Efektivitas pembelajaran teams games tournament berbasis permainan ludo bahasa terhadap penguasaan kosakata siswa kelas III - Wardana, Ilham Gigih Arif Setya; Rukayah, Rukayah Rukayah; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2024)
This research is motivated by a learning system that is not yet innovative, learning models that are not yet diverse, the lecture method makes students inactive and less brave when learning. The aim of this research is to determine the effect of the TGT learning model based on the ludo language game on vocabulary mastery in class III of SD Negeri IV Wonogiri. This type of research is experimental research with a One Group Pretest Posttest Design. The sample in this study consisted of 26 students. The data analysis technique is statistical using SPSS 23 with a normality test using the One-Sample Kolmogorov-Smirnov Test, the homogeneity test in this study uses the variance homogeneity test with the SPSS 23 program, and the paired t-test. The normality test results obtained a sig value of 0.200 > 0.05 indicating the data was normally distributed and the homogeneity test results obtained a sig value of 0.656 > 0.05 indicating the research data was homogeneous. The results of this research prove that the TGT learning model assisted by the ludo game media has an effect on vocabulary mastery, obtaining a sig (2-tailed) value of 0.004 < 0.05. The conclusion obtained is that there is a significant difference between the pretest and posttest.